Health Behavior Theory in Popular Calorie Counting Apps: A Content Analysis - Davis, Siena F; Ellsworth, Marisa A; Payne, Hannah E; Hall, Shelby M; West, Joshua H; Nordhagen, Amber L (JMIR Publications, 2016)
BackgroundAlthough the Health & Fitness category of the Apple App Store features hundreds of calorie counting apps, the extent to which popular calorie counting apps include health behavior theory is unknown. ObjectiveThis study evaluates the presence of health behavior theory in calorie counting apps. MethodsData for this study came from an extensive content analysis of the 10 most popular calorie counting apps in the Health & Fitness category of the Apple App Store. ResultsEach app was given a theory score to reflect the extent to which health behavior theory was integrated into the app. The highest possible score was 60. Out of the 10 apps evaluated, My Diet Coach obtained the highest theory score of 15. MapMyFitness and Yumget received the lowest scores of 0. The average theory score among the apps was 5.6. ConclusionsMost of the calorie counting apps in the sample contained minimal health behavior theory.